2015
DOI: 10.1109/tcpmt.2015.2434273
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Stage Process for Laser Prototyping of Microwave Circuits in LTCC Technology

Abstract: Abstract-An improved technique for laser prototyping of microwave circuits in LTCC technology is presented. This builds on previous work which demonstrated that laser machining of conductor layers on unfired LTCC tape could be used to fabricate multilayer microwave circuits without any patterned screens, stencils or masks. The improved process employs post-fire patterning of the top and bottom layer. In this way, sensitive microwave structures like couplers and filters can be fabricated on the outer layers bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…In contrast to our previous work, where the entire SRR pattern was screen-printed, we used laser ablation to pattern the interelectrode gap and in some cases, the entire SRR. Laser ablation allows for much finer features than that which are achievable using screen-printing [38,39]. Due to the different fabrication techniques and gap sizes, we found that the resonant frequency of SRRs in this study varied from ∼2.6 to 2.9 GHz.…”
Section: Srr Fabricationmentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast to our previous work, where the entire SRR pattern was screen-printed, we used laser ablation to pattern the interelectrode gap and in some cases, the entire SRR. Laser ablation allows for much finer features than that which are achievable using screen-printing [38,39]. Due to the different fabrication techniques and gap sizes, we found that the resonant frequency of SRRs in this study varied from ∼2.6 to 2.9 GHz.…”
Section: Srr Fabricationmentioning
confidence: 71%
“…The use of fs-and ns-laser ablation differs mainly in that ns-laser ablation is expected to be a much more thermal process whereas fs-laser ablation can be athermal [37]. Both methods are expected to produce microstrip sidewalls with better verticality and smaller features than screen printing [38,39]. These fabrication techniques can also produce different microstructural features in the interelectrode gap.…”
Section: Introductionmentioning
confidence: 99%
“…MCM proved very useful as a lowcost solution without forfeiting significant performance requirements. MCM modules employing low-temperature cofired ceramics (LTCC) and organic thin film have been remained especially popular in recent decades in RF and millimeterwave applications [9][10][11] . Multichip modules are the most generalized of the other advanced packaging solutions.…”
Section: Multichip Module (Mcm)mentioning
confidence: 99%